Optimalisasi Proses Produksi dan Manajemen Usaha Dalam Rangka Peningkatan Produktivitas Laundry - Zaharuddin, Zaharuddin; Nurjamiyah, Nurjamiyah; Saragih, Edy Syahputra (JPM: Jurnal Pengabdian Masyarakat, 2025)
Deli Serdang is a regency located in North Sumatra Province. One of the villages in Deli Serdang Regency is Tembung Village. Based on the available resources in Deli Serdang, especially in Tembung Village, there is great potential for business development. One of the businesses in Tembung Village is a laundry service business that was started in 2018 by Mr. Ahmad. Based on the results of a survey that has been conducted, the proponent has designated Mr. Ahmad's laundry business group as a partner. The proponent and the partner have agreed on several issues that have been faced by the partner, including the drying stage, which takes a long time due to limited equipment. Until now, the drying process has been inadequate, still relying on traditional drying methods, namely sunlight. Electric irons use heating elements on metal plates directly. This has many shortcomings, especially in terms of quality. It can damage certain clothes, such as burning or shining clothes. This is usually because the electric iron used is too hot. Thirdly, laundries still use manual record-keeping methods such as notebooks, so that data is not integrated in real time. In general, profit and loss calculations, financial reports, and clothing inventory records are still done on paper. The objectives of this PKM activity are to provide information, training, and assistance to partners on: 1) Making clothes dryers; 2) Making steam-based clothes ironing tools; 3) Creating a Laundry Management Web Application. The targeted outcomes of this Community-Based Empowerment Program are: 1) Increased production process efficiency with the use of drying machines and steam irons, as partners will have the knowledge to use these machines, thereby helping them speed up the drying process and eliminating the need for tedious sun drying. Clothes are ironed faster, neater, and free from the risk of damage; 2) With the laundry management software, partners have knowledge of how to use the application, namely profit and loss calculations, financial reports, and data collection on clothes coming in and out. Scientific articles will be published in the form of accredited journals and publications in online media and videos of Community-Based Empowerment Activities.